2005
DOI: 10.1111/j.1365-2419.2005.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile chinook salmon (Oncorhynchus tshawytscha) growth on the central California coast during the 1998 El Niño and 1999 La Niña

Abstract: We assessed growth in subyearling chinook salmon (Oncorhynchus tshawytscha) during the 1998 El Niñ o and 1999 La Niñ a in the Gulf of the Farallones, a region of the continental shelf off central California seaward of the Golden Gate and the southernmost ocean entry point for the species in North America. Juvenile salmon demonstrated greater growth during this strong El Niñ o, when water temperature anomalies of more than +3°C were recorded at local buoys, than during the similarly strong 1999 La Niña.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…While we observed higher growth rates in the multi-habitat enclosure, all growth rates (>1.1 mm/d for both enclosures) were very high compared with published data for juvenile salmon growth in California. In the Yolo Bypass, published apparent growth rates range from 0.52 to 0.80 mm/d (Sommer et al 2001), with a similar range reported for subyearling Chinook Salmon growth on the central California coast (MacFarlane et al 2005). Therefore, despite the significant difference between enclosures, the growth rates we observed were so much higher than what has been reported in previously published work that the ecological difference is likely negligible and does not signal physiological stress in the downstream comparison enclosure.…”
supporting
confidence: 82%
“…While we observed higher growth rates in the multi-habitat enclosure, all growth rates (>1.1 mm/d for both enclosures) were very high compared with published data for juvenile salmon growth in California. In the Yolo Bypass, published apparent growth rates range from 0.52 to 0.80 mm/d (Sommer et al 2001), with a similar range reported for subyearling Chinook Salmon growth on the central California coast (MacFarlane et al 2005). Therefore, despite the significant difference between enclosures, the growth rates we observed were so much higher than what has been reported in previously published work that the ecological difference is likely negligible and does not signal physiological stress in the downstream comparison enclosure.…”
supporting
confidence: 82%
“…Because of uncertainty in determining the time of movement of fish from the freshwater to the estuary and the estuary to the ocean from scales, we combined the first year of growth in the analyses. Importantly, it has been demonstrated that some Chinook salmon populations have substantial inter‐annual variation in their period of estuarine residence that is dependent on some of the same environmental variables we are examining (MacFarlane et al. , 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The mass increment of salmonids increases rapidly after entering sea water (Jonsson & Jonsson, 2003), and temperature appears to be one of the major abiotic factors influencing growth. Investigations of O. tshawytscha in the Gulf of the Farallones, central California, revealed that post‐smolts grew better and had higher energy storage in a warm year with reduced salinity and elevated zooplankton productivity than in colder years with higher salinity (Macfarlane et al , 2005). Similarly, the growth increment of the one‐sea‐winter S. salar was higher in years with large areas with relatively high water temperature and high North Atlantic Oscillation index (NAOI) in May, the month when the smolts moved to sea (Friedland et al , 2000; Jonsson & Jonsson, 2004 b ).…”
Section: Growthmentioning
confidence: 99%